Qualitative inquiry & research design : choosing among five approaches - Creswell, John W.; Poth, Cheryl N. (Thousand Oaks, California : Sage, 2023)
"We are delighted to offer a fully updated fifth edition of this book. In this newest edition, John along with Cheryl (who joined as a coauthor on the fourth edition) offer updated examples and guidance on designing qualitative research across five approaches. The work on this book spans almost three decades with each edition reflecting evolutions in qualitative research. The primary purpose of this book is to introduce qualitative research and highlight five approaches to inquiry. In this way, readers can see options for conducting research and select the best option for their studies"--
Appendix A. A Narrative Research Study--"Living in the Space Between Participant and Researcher as a Narrative Inquirer: Examining Ethnic Identity of Chinese Canadian Students as Conflicting Stories to Live By" / Elaine Chan -- Appendix B. Resilient Leadership: A Phenomenological Exploration Into How Black Women in Higher Education Leadership Navigate Cultural Adversity / Nuchelle L. Chance -- Appendix C. Aging With Intellectual Disability in Families: Navigating Ever-Changing Seas--A Theoretical Model / Henrietta Trip, Lisa Whitehead, Marie Crowe, Brigil Mirfin-Veitch and Chris Daffue -- Appendix D. An Ethnography--"British-Born Pakistani and Bangladeshi Young Men: Exploring Unstable Concepts of Muslim, Islamophobia, and Racialization" / Martin Mac an Ghaill and Chris Haywood -- Appendix E. Learning from Error in Violence Prevention: A School Shooting as an Organizational Accident / Sarah Goodrum, Jessie Slepicka, William Woodward and Beverly Kingston.
Includes bibliographical references and index.
Keywords: Social sciences -- Methodology; Research -- Design; Experimental design; Qualitative research